The Role of Botulinum Neurotoxin A in the Conservative Treatment of Fractures: An Experimental Study on Rats - Themistoklis Vampertzis; Christina Barmpagianni; Chryssa Bekiari; Georgia D. Brellou; Ioannis A. Zervos; Eleftherios Tsiridis; Nikiforos Galanis (The Scientific World Journal)
This paper explores the role of botulinum neurotoxin in aiding fracture recovery through temporary muscle paralysis. Specifically, it investigates the effects of botulinum neurotoxin-induced paralysis of the sternocleidomastoid muscle on clavicle fractures in rats. The research aims to assess safety, effectiveness, and the impact on fracture healing. Healthy male Albino Wistar rats were divided into four groups: clavicle fracture, botulinum neurotoxin injection, both, and control. Surgeries were conducted under anaesthesia, and postoperatively, animals were monitored for 28 days. Euthanasia and radiological assessment followed, examining fracture healing and muscle changes, while tissues were histopathologically evaluated. The modified Lane–Sandhu scoring system was used for the radiographic evaluation of clavicle fractures, and the results varied from complete healing to nonunion. Histopathological examination at 28 days postfracture showed fibrous tissue, mesenchymal cells, and primary callus formation in all groups. Despite varied callus compositions, botulinum neurotoxin administration did not affect clavicle healing, as evidenced by similar scores to the control group. Several studies have explored botulinum neurotoxin applications in fracture recovery. Research suggests its potential to enhance functional recovery in certain types of fractures. Theoretical benefits include managing muscle spasticity, aiding reduction techniques, and preventing nonunion. However, botulinum neurotoxin’s transient effect and nonuniversal applications should be considered. The present study found that botulinum toxin had no clear superiority in healing compared to controls, while histological evaluation showed potential adverse effects on muscle tissue. Further research is essential to understand its risk-benefit balance and long-term effects.